Living Expectations of Rural Women with a Foreign Husband: A Case of Northeast, Thailand - อายุวัฒน์ ดุษฎี; ณรงค์ชัย วณิชชา (Ratchaphruek Journal, 2018)
This research was aimed at studying: 1) preparation of women who were travelling to marry foreigners and their expectations of living with their husbands, and 2) factors correlated to the levels of expectations of living with their husbands in the destination country. The quantitative method was applied and the target group consisted of 211 women living in Udonthani and Khon Kaen who were going abroad to marry foreigners. The number of women in these two areas has shown high potential in cross-national marriage. The data were collected through the structured interview during June to August 2011. Pearson Correlation Analysis was completed to determine correlation between the factors. The results show that women who were going to marry a foreigner had language, social and cultural preparation for their lives abroad. Preparation in terms of knowledge on their rights after marriage, needs of assistance while living abroad, and financial management was found at a low level. However, the majority’s expectations of living with their foreign husband were at a medium level; roughly half had great expectations of security, sustainability, honest spouse who trust them, and spouses’ assistance in their adjustment. Moreover, one third of the target groups expected their foreign husband to provide financial assistance to support their parents and family back home. The factors correlated significantly to expectations of living with a foreign husband included the degree of preparation before travelling and the income per month.